Corporate Social Responsibility and Financial performance in Centenary Bank - main branch. A Cross-sectional study. - Miria Birungi; Edmand Bakashaba (Student's Journal of Health Research, 2022)
Background: The purpose of this study was to examine the relationship between Corporate Social Responsibility and the Financial performance of Centenary Bank, main branch by examining the relationship between philanthropic responsibility and financial performance, establishing the relationship between economic responsibility and financial performance, and assessing the relationship between ethical responsibility and financial performance of Centenary bank.  Methodology This study followed a descriptive correlational and cross-sectional survey design and adopted a quantitative paradigm. The researcher collected data from a sample of 132 employees using a self -administered questionnaire.  Results: The study findings revealed that 52% of the corporate social responsibility activities of the centenary bank are economical, followed by 37% of the corporate social responsibility were ethical and 11% of its corporate social responsibilities were philanthropic. There was a significant relationship (r=0.4, sig=0.00) between philanthropic responsibility and the financial performance of Centenary bank. There was also a negative significant (r= -0.374, sig=0.045) relationship between economic responsibility and the financial performance of Centenary bank. There was a positive significant relationship between ethical responsibility and the financial performance of Centenary bank.  Conclusion: Generally, there is a relationship between corporate social responsibility and the financial performance of the Centenary bank.  Recommendation:  Centenary banks should engage in philanthropic activities to maintain a good reputation through supporting the Kabaka run and providing piped water, and scholarships to unprivileged children. Centenary bank should also be effective in communicating with stakeholders, ensuring the safety of customer balances, and offering quality customer service to attract more customers for its financial growth. Centenary bank should also reduce its expenditure on non-productive activities like bonuses and travel allowances for senior staff to reduce the significant unnecessary expenditure.